2013
DOI: 10.1002/mrm.24997
|View full text |Cite
|
Sign up to set email alerts
|

Calibrationless parallel imaging reconstruction based on structured low-rank matrix completion

Abstract: Purpose A calibrationless parallel imaging reconstruction method, termed simultaneous auto-calibrating and k-space estimation (SAKE), is presented. It is a data-driven, coil-by-coil reconstruction method that does not require a separate calibration step for estimating coil sensitivity information. Methods In SAKE, an under-sampled multi-channel dataset is structured into a single data matrix. Then the reconstruction is formulated as a structured low-rank matrix completion problem. An iterative solution that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
496
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(500 citation statements)
references
References 34 publications
4
496
0
Order By: Relevance
“…In both approaches, an accurate estimation of coil sensitivity maps or GRAPPA kernel is essential to fully exploit the coil sensitivity diversity. In order to overcome these difficulties, calibration-less parallel imaging methods have been extensively investigated, among which SAKE (simultaneous autocalibrating and k-space estimation) [16] represents one of the first steps. In SAKE, the missing k-space elements are reconstructed by imposing the data consistency and the structural maintenance constraints of the block Hankel structure matrix.…”
Section: A[s R ]mentioning
confidence: 99%
See 3 more Smart Citations
“…In both approaches, an accurate estimation of coil sensitivity maps or GRAPPA kernel is essential to fully exploit the coil sensitivity diversity. In order to overcome these difficulties, calibration-less parallel imaging methods have been extensively investigated, among which SAKE (simultaneous autocalibrating and k-space estimation) [16] represents one of the first steps. In SAKE, the missing k-space elements are reconstructed by imposing the data consistency and the structural maintenance constraints of the block Hankel structure matrix.…”
Section: A[s R ]mentioning
confidence: 99%
“…In compressed sensing MRI, the reconstruction image grid is always fixed; therefore, cardinal spline model that has knot locations on a fixed grid is more appropriate. Therefore, the results in (16) implies that the required number of samples are proportional to the sparsity level up to log 2 (n) factor. Considering that the standard compressed sensing analysis showed that the required number of Fourier samples in the l 1 minimization approach is proportional to the sparsity level up to log q (n) factor for some integer q [1], [2], the result in (16) is comparable to the standard CS-MRI approach.…”
Section: Sampling Rate Stability and Compressibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the intuitive sampling, the MC framework has been considered for a variety of signal recovery problems including collaborative spectrum sensing [19], sensor localization [20,21], and image reconstruction problems [22,23] among others. MC has been recently explored as a sampling scheme for WSNs [24][25][26][27].…”
Section: Related Workmentioning
confidence: 99%